(untitled) (Research, Society and Development, 2020)
Objective: To identify the knowledge of high school students in a school in the city of Santarém-PA about Diabetes mellitus, and to highlight the importance of computerization and knowledge about the disease. Methodology: this is a quantitative study with descriptive approach, starting from the observation of reality, followed by the definition of the problem, theorization, construction of solution hypotheses and subsequent application of a questionnaire and intervention through a lecture according to the Manguerez Arch. The questionnaire addressed questions related to DM, making it possible to identify the students’ knowledge about it. Results: We interviewed 56 high school students, aged 15 to 28 years, in which a questionnaire was applied used for data collection, which addressed socio-demographic characteristics and students’ knowledge about DM. Conclusions: It was found that most of the research participants are aware of DM, how to acquire it and what the consequences of the disease are.